Autonomous MEMS Inclinometer - Alves, F. S. (2012)
Pull-in voltage measurements are used in this work as the transduc-tion mechanism to build a novel microelectromechanical system (MEMS) incli-nometer. By successively bringing the microstructure to pull-in while measur-ing the pull-in voltage allows the detection of external accelerations. Moreover, the availability of asymmetric pull-in voltages that depend on the same mechan-ical structure and properties enables the implementation of an auto-calibrated thermal compensated inclinometer. The thermal compensation method is de-scribed and it relies on the measurement of pull-in voltages only. Both simulations and experiments are used to validate this novel approach and first results show a sensitivity of 50mV/º and a resolution of 0.006º